Ranah Sumber Binatang dalam Panyandra: Menjadi Cantik ala Orang Jawa (Sutasoma : Jurnal Sastra Jawa, 2023)
Panyandra is a form of expression in Javanese which is used to praise someone's beauty or beauty. Panyandra in Javanese society is usually to praise the bride (nyandra manten). Panyandra is a form of metaphor because it has metaphorical components such as the target domain, the source realm and the mapping between the target realm and the source realm. An interesting thing to study is the use of the source domain in panyandra. If panyandra is used to praise the beauty, however, the source realm used as a comparison looks far from beauty. An example is the use of the beast's source realm. Panyandra as a form of metaphor in Javanese can be used as an expression of the human conceptual system in thinking. This is based on the understanding that metaphor can be a reflection of the cognition and culture of a speech community. Thus, this study aims to describe the use of the animal source domain in panyandra as a form of cognitive process to understand the concept of female beauty according to the Javanese view. This study used descriptive qualitative method. Data sources are limited to pannyandra. Data collection was carried out using the observing and noting method so that the panyandra was collected in the form of sentences. Next, the data is analyzed to classify panyandra as a metaphor based on the animal source domain and the mapping pattern of the beauty metaphor using the animal source domain. The theoretical framework used as the basis for thinking in this study is a conceptual metaphor; the relationship between language, culture and thought; and analysis of meaning components. The results obtained are that there are various types of animals that are used as source domains, namely insects, wild animals, birds, and reptiles. There is a pattern of mapping relationships between the target domain and the source domain, namely through the properties of both of them are defined socio-culturally, then the two domains are mapped. Keywords: panyandra; metaphor; the beauty; Javanese woman; animal lexicon